Behavior of CFS shear walls infilled with lightweight ceramsite concrete under cyclic loading. (November 2022) - Wang, Jiqin; Zhou, Tianhua; Nie, Shaofeng; Zhang, Xudong; Shao, Yinghao
Abstract: To meet the lateral resistance requirement for cold-formed steel (CFS) shear walls in multistory buildings, a novel CFS shear wall filled with lightweight ceramsite concrete is proposed in this paper. Three full-scale specimens were conducted under cyclic loading to evaluate their failure mode, bearing capacity, lateral stiffness, ductility, and energy dissipation. The experimental results showed that the main failures of the walls were bond-slip cracks between the CFS framing and fillers, cracking of sheathings, and compression failure at the corners of the fillers. The bearing capacity and energy dissipation of the infilled walls were superior to that of unfilled wall. Increasing the stud section area could improve the lateral behavior of the wall. Finite element (FE) models were introduced to simulate the shear performance of the test specimens. The numerical simulation results were in good agreement with the experimental results; hence, the FE models for simulating CFS shear walls were validated. Subsequently, a parametric study was performed by varying the parameters, including the ceramsite concrete strength, wall thickness, aspect ratio, steel strength, and sheathing material. Furthermore, a calculation method was proposed to determine the bearing capacity of the CFS shear walls. The calculated results agree well with the experimental results. A comparison between the proposed CFS shear walls and existing CFS shear walls showed that the lateral performance of the proposed walls was higher than that of CFS shear walls.